Midgut bacterial communities in the giant Asian honeybee (Apis dorsata) across 4 developmental stages: A comparative study - Saraithong P. (2017)
© 2015 Institute of Zoology, Chinese Academy of Sciences Bacterial communities are known to play important roles during the developmental stages of insects, but current knowledge of bacteria associated with the midgut of Apis dorsata, the giant Asian honeybee, is limited. Using polymerase chain reaction-denaturing gradient gel electrophoresis analysis (PCR-DGGE) and 16S rRNA sequencing, the aim of this study was to determine the dynamics of bacterial community structure across four A. dorsata life stages in different geographical locations. The results reveal that bacterial diversity increased as the bee progressed through larval stage to newly emerged worker and old worker. However, in the pupal stage, no bands identified as bacteria could be observed. Overall, 2 bacterial phyla (Proteobacteria and Firmicutes) and 4 classes (Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, and Bacilli) were identified, but the frequency varied among the different stages and locations. The classes of Gammaproteobacteria and Bacilli dominated among larval, newly emerged worker and old worker developmental stages.